The use of controlled punishment and ritual in couples therapy - Lynch, B.J. (The Therapist's Notebook: Homework, Handouts, and Activities for Use in Psychotherapy, 2013)
Couples who come into therapy with amorphous symptoms often reveal later in treatment that there has been a traumatic event that occurred in the past and that has lingered as a significant disturbance to intimacy. No amount of “talk therapy? or insight seems to allow these couples to move past the point of emotional treachery. This activity is designed to allow these couples a vehicle for putting the past to rest in a way that allows them to continue their relationship without resentment, revenge, or continual pain. © 1998 by The Haworth Press, Inc. All rights reserved.
Journal Abbreviation: The Therapist's Noteb.: Homework, Handouts, and Activities for Use in Psychotherapy
Keywords: dept.mft

Fat in school: applied interdisciplinarity as a basis for consultation in oppressive social context - Clare, Mary M.; Ardron-Hudson, Elise A.; Grindell, Jessica (Journal of Educational and Psychological Consultation, 2015)
Children and youth in schools are subject to the effects of the larger culture's attitudes and values related to body size. When negatively biased, these attitudes and values can have detrimental effects and thus emerge as relevant to educational and psychological consultants. Drawing on the nascent field of Fat Studies with its focus on the cultural meanings attached to large bodies, we identify direct implications of fat phobia for school-age children and youth. Via a brief case example, an initial review of literature, and several examples of health-positive programming, we describe the social justice implications of fat phobia for consultants in school and community settings. In this consideration of the role of consultants for addressing fat bias and supporting health, we also suggest the merit of applied interdisciplinarity as a strong ground for consultation research and practice. The academic area of Fat Studies provides illustration of the integration of disciplinary perspectives (e.g., sociology, anthropology, biology, psychology). Educational and psychological consultation is ideally situated for systematically engaging such interdisciplinarity in support of practical outcomes that are healthy, sustainable, and socially just.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/016-800-206-439-585 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: dept.mft

Theory into research practice: reflections and recommendations on collaborative feminist research - Harvey, Rebecca G.; Brown, Kristina S.; Miller, Bobbi J.; Williams-Reade, Jacqueline; Tyndall, Lisa; Murphy, Megan J. (Journal of Feminist Family Therapy, 2016)
Six women faculty came together to research their peers asking other women in COAMFTE-accredited programs about their personal and professional identities. The goal of this research was to develop recommendations for the field of Couple/Marriage and Family Therapy to support the engagement and advancement of women faculty. The research collaboration itself became a heuristic, feminist praxis, a co-creation of insight, support network, and professional relationships which had liberating results for the collaborators. We intended to create a research project that would be collaborative, empowering, and transformative for participants; in the process, the collaboration became empowering and transformative for ourselves. This article will reflect on our experiences and provide recommendations for future feminist research teams. Copyright © Taylor & Francis Group, LLC.
6 citations (Crossref) [2023-10-31] Citation Key Alias: pop00155 tex.type: [object Object]
Keywords: clinical article; collaboration; dept.mft; family therapy; female; feminism; feminist research; gender; human; insider/outsider; marriage; university

Queer youth in family therapy - Harvey, Rebecca G.; Fish, Linda Stone (Family Process, 2015)
Trends in popular belief about same-sex relationships have undergone noteworthy change in the United States over the last decade. Yet this change has been marked by stark polarizations and has occurred at varying rates depending upon regional, community, racial, religious, and individual family context. For queer youth and their families, this cultural transformation has broadened opportunities and created a new set of risks and vulnerabilities. At the same time, youth's increasingly open and playful gender fluidity and sexual identity is complicated by unique intersections of class, race, religion, and immigration. Effective family therapy with queer youth requires practitioner's and treatment models that are sensitive to those who bear the burden of multiple oppressions and the hidden resilience embedded in their layered identities. We present case examples of our model of family therapy which addresses refuge, supports difficult dialogs, and nurtures queerness by looking for hidden resilience in the unique intersections of queer youths' lives. These intersections provide transformational potential for youth, their families and even for family therapists as we are all nurtured and challenged to think more complexly about intersectionality, sexuality, and gender. Las tendencias en la creencia popular acerca de las relaciones entre personas del mismo sexo han sufrido un cambio considerable en Estados Unidos durante la ultima decada. Sin embargo, este cambio se ha producido a ritmos diferentes segun las comunidades locales y regionales, y el contexto familiar individual. En el caso de los jovenes queer y sus familias, esta transformacion cultural ha ampliado oportunidades y creado un nuevo conjunto de riesgos y vulnerabilidades. Los jovenes queer y sus familias, al intentar desarrollarse en numerosos contextos, estan marcados por divergencias crueles en actitudes y creencias. Al mismo tiempo, la fluidez del genero y la identidad sexual cada vez mas abiertas y ludicas de los jovenes estan complicadas por intersecciones unicas de clase, raza, religion e inmigracion. Una terapia familiar eficaz con jovenes queer exige modelos de tratamiento y profesionales que sean sensibles a aquellas personas que cargan sobre sus espaldas numerosas opresiones y una resiliencia oculta incorporada en sus identidades multiples. Presentamos ejemplos de casos de nuestro modelo de terapia familiar que aborda el refugio, respalda los dialogos dificiles y apoya la sexualidad alternativa buscando la resiliencia oculta en las intersecciones unicas de las vidas de los jovenes queer. Estas intersecciones ofrecen posibilidades transformacionales para los jovenes, sus familias e incluso los terapeutas familiares mientras nos estimulan y nos desafian a todos a pensar de forma mas compleja acerca de la interseccionalidad, la sexualidad y el genero.
22 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/008-905-145-849-804 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Adolescent; Family Relations; Family Therapy; Family therapy; Female; Gay; Gender Identity; Homosexuality; Homosexuality; Female; Homosexuality; Male; Humans; Interpersonal Relations; Lesbian; Male; Resilience; Social Identification; Social Isolation; Transgender Persons; Transgendered youth; United States; Vulnerable Populations; Young Adult; adolescent; dept.mft; family relation; family therapy; female; gender identity; homosexuality; human; human relation; lesbianism; male; male homosexuality; procedures; psychology; social behavior; social isolation; statistics and numerical data; transgender; vulnerable population; young adult

Substance abuse prevention: perspectives from india’s addiction treatment professionals - Perumbilly, Sebastian A; Anderson, Stephen A (American Journal of Sociology, 2015)
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/045-554-955-113-014 tex.type: [object Object]
Keywords: dept.mft; peer-reviewed

Using CBPR methods in college health research exploring excessive alcohol consumption - Bulmer, Sandra Minor; Barton, Barbara A; Liefeld, Julie; Montauti, Sara; Santos, Stephanie; Richard, Melissa; Hnath, Laura; Pelletier, Kara; Lalanne, Jude (Journal of Adolescent Research, 2016)
Community-based participatory research (CBPR) is a collaborative methodology that uniquely involves stakeholders in all stages of the research process. CBPR has been widely utilized in the field of public health, but not widely employed with college populations. This study utilized CBPR methods within a college community to gain insight into excessive alcohol consumption. Six student researchers planned and carried out a rigorous qualitative study at a public university in the Northeast region of the United States. A total of 48 undergraduate participants were recruited for focus groups that were facilitated by two student researchers, and transcribed and analyzed using thematic analysis methods. Students' reasons for drinking alcohol were focused within the themes of inclusion, habitual default, and the student development process. Social media, strict policy/enforcement, and student's desire to avoid responsibility led to increased risk and consequences related to drinking. Students recommended late night transportation and a Good Samaritan policy as strategies to improve student safety. This study led to student advocacy and policy change directed at improving student's health and safety and demonstrated that CBPR methods show promise for engaging students and producing meaningful data.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/015-321-517-465-575 tex.type: [object Object]
Keywords: college issues; dept.hhs; dept.mft; emerging adulthood; health; qualitative methods; substance use

Facilitators and barriers in treatment seeking for substance use disorders: indian clinical perspectives - Perumbilly, Sebastian A.; Melendez-Rhodes, Tatiana; Anderson, Stephen A. (Alcoholism Treatment Quarterly, 2018)
Despite great advances that have been made in the understanding and treatment of substance use disorders (SUDs), fewer than 11% of eligible patients seek treatment. Few studies have explored the roles of facilitators and barriers in treatment seeking from the perspectives of addiction-focused clinicians working in developing countries. This descriptive study used a mixed-methods research design with concurrent strategies. Research participants were addiction-focused clinicians (N = 112) working in India. Primary research questions examined (1) key facilitators that motivate patients to seek treatment, (2) major barriers in treatment seeking, and (3) critical strategies for enhancing treatment seeking with the support of family, friends, and community. Key facilitators of treatment seeking included informed and caring family members, friends, and community. The most common barriers were patients’ denial of the problem of SUDs, shame in admitting the problem, and belief and confidence that they can quit using substances by themselves anytime. A systemically focused public awareness creation strategy, implemented simultaneously at various key sectors in society, was recommended for facilitating treatment seeking and removing barriers. Implications for clinicians, patients, public health personnel, community leaders, and regional, national, and global policy makers are reviewed. © 2018, © 2018 Taylor & Francis.
2 citations (Crossref) [2023-10-31] Citation Key Alias: pop00185 tex.type: [object Object]
Keywords: Addiction treatment; Article; India; adult; aged; awareness; barriers to treatment; clinician; community; dept.mft; drug dependence; facilitators of treatment; female; help seeking behavior; human; male; peer-reviewed; social stigma; substance use disorders; treatment seeking

“To feel him love me”: Emerging intersections of identity, queerness, and differing ability - Harvey, Rebecca (Gender, sex, and sexuality among contemporary youth, 2017)
AbstractOriginality/value This paper provides an alternative approach to nurturing queer identity by (1) creating refuge for emerging sexualities; (2) allowing for difficult dialogues where ability, sexuality, and gender can be pragmatically discussed, performed, and negotiated; (3) tolerating the discomfort of these difficult dialogues and pushing through to nurturing the unique queerness that evolves out of these conversations; and finally (4) encouraging transformation of all participants including client and practitioners. The practitioners discuss their own transformation through the co-created dialog with each other and with the client.
Keywords: Disability; Gay; Gay couple; Intersectionality; Queer; dept.mft; dept.swk

Indian perspectives on treating substance use disorders - Perumbilly, Sebastian A; Anderson, Stephen A (Alcoholism Treatment Quarterly, 2017)
Although research on substance use disorders (SUDs) largely focuses on the developed world, treatment programs from the developing world seldom get international attention. Focusing on India, this study was designed (1) to describe India’s treatment programs, and (2) to report Indian perspectives on critical factors related to treating SUDs. An online survey instrument was created, based on mixed-methods approach with concurrent strategies, to collect data. Participants were India’s clinicians (N = 112). Indian treatment approach suggests that SUDs must be treated by a multidisciplinary treatment team with a comprehensive plan that must include systemically focused clinical interventions in patients’/clients’ relevant relational systems. Findings may have relevance to clinicians, researchers, and policy makers globally. © 2017 Taylor & Francis.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/064-482-460-077-460 tex.type: [object Object]
Keywords: Addiction treatment; India; Indian; Note; adult; aged; clinical assessment; comparative study; controlled study; critical factors; dept.mft; drug dependence; family therapy; female; health survey; human; involving families; major clinical study; male; peer-reviewed; professional development; substance use disorders

Parents’ personal growth: expanding the view of therapy for child behavioral problems - Perumbilly, Sebastian A; Anderson, Stephen A; Boylin, William M (Journal of Family Psychotherapy, 2017)
Parenting literature often focuses on parental strategies that promote positive behavioral outcomes for children, but ignores key aspects of parents’ own growth process. This article presents a critical review of current literature on parenting and highlights the importance of focusing on parents’ growth in therapy. A clinical framework to define parents’ growth is offered along with case vignettes and practical guidelines for clinicians in order to assess parents’ growth. © 2017 Taylor & Francis Group, LLC.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/000-695-656-280-425 tex.type: [object Object]
Keywords: Article; Couple intimacy; behavior therapy; child behavior; child care; child parent relation; dept.mft; education program; family therapy; growth; human; intimacy; medical literature; parental attitude; parenting; parents’ growth; personal growth; personal needs; practice guideline; problem behavior; responsibility; self care; social isolation; training; vignette

Lesbian couples - Stone Fish, Linda; Harvey, Rebecca (Encyclopedia of couple and family therapy, 2017)
Keywords: Current Political Climate; Difficult Dialogue; Donor Insemination; LGBTQ Community; Lesbian Couple; dept.mft